2017
DOI: 10.1021/acsami.7b00759
|View full text |Cite
|
Sign up to set email alerts
|

Topological Insulator Bi2Se3/Si-Nanowire-Based p–n Junction Diode for High-Performance Near-Infrared Photodetector

Abstract: Chemically derived topological insulator BiSe nanoflake/Si nanowire (SiNWs) heterojunctions were fabricated employing all eco-friendly cost-effective chemical route for the first time. X-ray diffraction studies confirmed proper phase formation of BiSe nanoflakes. The morphological features of the individual components and time-evolved hybrid structures were studied using field emission scanning electron microscope. High resolution transmission electron microscopic studies were performed to investigate the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 59 publications
(100 reference statements)
0
38
0
1
Order By: Relevance
“…The maximum on–off ratio of this device is 5.32 × 10 4 @ 650 nm, which is more than two orders of magnitude higher than similar devices previously reported ( Table 1 ). Therefore, the device has more distinguished I – V rectification characteristics than other reported devices based on TIs materials. In Bi 2 Se 3 /MoO 3 heterojunction, the Fermi energy level ( E f ) of N‐type material Bi 2 Se 3 is −5.3 eV and the bandgap is 0.3 eV.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The maximum on–off ratio of this device is 5.32 × 10 4 @ 650 nm, which is more than two orders of magnitude higher than similar devices previously reported ( Table 1 ). Therefore, the device has more distinguished I – V rectification characteristics than other reported devices based on TIs materials. In Bi 2 Se 3 /MoO 3 heterojunction, the Fermi energy level ( E f ) of N‐type material Bi 2 Se 3 is −5.3 eV and the bandgap is 0.3 eV.…”
Section: Resultsmentioning
confidence: 88%
“…By measuring the response time of the device, the optical response performance is deeply studied. Impressively, the response time reached a staggering 62 µs, better than many previously reported IR devices at room temperature . The heterogeneous structure based on Bi 2 Se 3 has great application potential in the field of photoelectric detection, which provides a feasible direction for the application of 3D TIs materials.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Besides, Bi 2 Te 3 and Bi 2 Se 3 are all stoichiometric rhombohedral materials with quintuple stacked layered structure and relatively weak layer‐to‐layer van der Waals coupling, as shown in Figure a. Therefore, high‐quality thin films can be easily deposited on the Si substrate via different techniques, making further basic studies and potential applications possible. More importantly, it was suggested that the construction of Bi 2 Se 3 on Si could introduce a very high Schottky barrier of ≈0.34 eV at the interface, which can be used to accelerate the separation of photo‐excited carriers in Si or Bi 2 Se 3 and inhibit their recombination simultaneously, thus the outstanding photoelectric responses were usually obtained.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23]25,27] However, for traditional PDs, researchers mainly concentrated on the longitudinal separation of photo-generated carriers in the interface of the heterojunctions, while the excellent surface transport properties were usually neglected or not well utilized. [21][22][23]25,27] However, for traditional PDs, researchers mainly concentrated on the longitudinal separation of photo-generated carriers in the interface of the heterojunctions, while the excellent surface transport properties were usually neglected or not well utilized.…”
mentioning
confidence: 99%